Electrochemical and Chemical Instability of Vanadium Nitride in the Synthesis of Ammonia Directly from Nitrogen. Issue 2 (29th October 2019) - Manjunatha, Revanasiddappa; Karajić, Aleksandar; Teller, Hanan; Nicoara, Katherina; Schechter, Alex
Abstract: Recently, vanadium nitride (VN) was proposed as an active catalyst for a challenging electrochemical nitrogen reduction reaction (NRR) to ammonia. In this study, the stability of vanadium‐nitride in electrolyte solutions of different pH values was studied under selected cathodic potentials. Intensive leaching of vanadium ions and nitrogen constituents into the bulk of the electrolyte solution was confirmed from ICP‐OES and UV‐Vis results. Abstract : Vanadium nitride : VN has been extensively used in various electrochemical applications such as in the field of electrochemical nitrogen reduction reaction, electrochemical supercapacitors, oxygen reduction reaction, etc. Present study shows the evidence of chemical and electrochemical instability of VN in acidic, neutral and alkaline electrolytes. The highest corrosion rate has been observed in alkaline solution, followed by acidic and neutral media respectively. Therefore, special attention needs to be taken when considering vanadium‐ or other transitional metal nitrides for electrochemical application.